If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8w + -10 = -3w + -10 Reorder the terms: -10 + 8w = -3w + -10 Reorder the terms: -10 + 8w = -10 + -3w Add '10' to each side of the equation. -10 + 10 + 8w = -10 + 10 + -3w Combine like terms: -10 + 10 = 0 0 + 8w = -10 + 10 + -3w 8w = -10 + 10 + -3w Combine like terms: -10 + 10 = 0 8w = 0 + -3w 8w = -3w Solving 8w = -3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '3w' to each side of the equation. 8w + 3w = -3w + 3w Combine like terms: 8w + 3w = 11w 11w = -3w + 3w Combine like terms: -3w + 3w = 0 11w = 0 Divide each side by '11'. w = 0 Simplifying w = 0
| 6x=458.80 | | 3d-d=16 | | f(-2)=-36-120x | | 8h-6h=12 | | -4x+3=-x+6 | | 13c-12c=7 | | -5(1x+8)=-80 | | 18g-16g=8 | | 7+3d=10 | | 9-(3x+6)=4-4x | | f(x)=70cos(6x^5) | | 8v-5v=9 | | 0.528*14.5= | | 3+6x-2x=8x-8+7x | | 4z*7+4=1 | | -m^2-15m=0 | | 7q+2(q-1)=71 | | 12u+-15u=9 | | 50=2.3+6.3 | | -6=-5x+4 | | 8(6x-8)=-304 | | 5y+9+2y=44 | | 4(1x-1)=-44 | | 12y+7=11 | | 3j+10=j-2 | | -5x-42=2x | | 8 = n3+ 4 | | 6t-2t-3t=13 | | 3x+2x+4=34 | | 10x+11y=-6 | | 3a-17=51 | | x^2+12x+6=-3-3x^2 |